Self-assessment questionnaire development for soft skills competency and core value evaluations - Al-Azmi, Abdul Rahman; Wan Nik, Wan Noor Nazayan; Embong, Zulmaryan; Che Ahmad, Aminudin; Muhammad, Siti Aesah Naznin; Kassin, Noor Lide Abu; Tauhed, Siti Zainab (International Journal of Public Health Science (IJPHS), 2024)
Soft skills play a vital role for providing excellent customer service in the healthcare setting. This study aims to develop and assess the instrument validity and reliability before measuring the levels of soft skills competency and core value internalization on staffs at the Sultan Ahmad Shah Medical Centre @International Islamic University Malaysia (SASMEC@IIUM). A self-assessment questionnaire was developed through three phases. The first phase involved reviewing and identifying relevant literatures and existing soft skills assessment instruments through bibliographic searches and expert consultations. A conceptual model was then established based on the selected conceptual frameworks after determining all relevant soft skill domains. The second phase involved generating relevant items, removing duplicate or irrelevant items, and appraising the content validity by three experts. The third phase was data collection, wherein the finalized instrument was distributed to 32 staff of SASMEC@IIUM via google forms. The instrument reliability was investigated through internal consistency reliability or Cronbach’s alpha, with all items, except for the construct ‘gratitude’, achieving acceptable values by exceeding the threshold value of 0.7. Subsequently, two gratitude items were removed from the questionnaire. The current instrument and theoretical framework employed in the self-assessment questionnaire development are valid and reliable for the actual application.